2021
DOI: 10.3389/fnbeh.2021.655029
|View full text |Cite
|
Sign up to set email alerts
|

Parafascicular Thalamic and Orbitofrontal Cortical Inputs to Striatum Represent States for Goal-Directed Action Selection

Abstract: Several lines of evidence accrued over the last 5–10 years have converged to suggest that the parafascicular nucleus of the thalamus and the lateral orbitofrontal cortex each represent or contribute to internal state/context representations that guide action selection in partially observable task situations. In rodents, inactivations of each structure have been found to selectively impair performance in paradigms testing goal-directed action selection, but only when that action selection relies on state repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Thus, although it is apparent that DMS circuits are incorporating signals from both the mOFC and prelimbic PFC, clarifying the distinct functional contribution of these different corticostriatal pathways remains an important question for future studies. This being said, an important consideration is that the effects of the pharmacological disconnections used here may reflect not only disruption of direct pathways between the mOFC and striatal targets but also through intermediary regions that share projections with these circuits, such as the basolateral amygdala or the parafascicular thalamus (Stayte et al, 2021).…”
Section: Mofc Fi Dms Circuitrymentioning
confidence: 99%
“…Thus, although it is apparent that DMS circuits are incorporating signals from both the mOFC and prelimbic PFC, clarifying the distinct functional contribution of these different corticostriatal pathways remains an important question for future studies. This being said, an important consideration is that the effects of the pharmacological disconnections used here may reflect not only disruption of direct pathways between the mOFC and striatal targets but also through intermediary regions that share projections with these circuits, such as the basolateral amygdala or the parafascicular thalamus (Stayte et al, 2021).…”
Section: Mofc Fi Dms Circuitrymentioning
confidence: 99%
“…However, it is difficult to clearly distinguish between selection functions and the other more integrative perceptual processes needed for the goal-directed guidance in which this subarea is involved. For example, recent studies have indicated that the lateral OFC is involved in the updating of outcome values and integrating specific external and internal perceptual presentations to achieve a goal (Baltz et al, 2018;Stayte et al, 2021). These studies lend weight to its putative perceptual role but do not differentiate the lateral and medial parts with respect to the integrative role that was suggested to be under the control of the medial areas in Ben Shalom's model.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous primate and rodent studies have shown that CM/PF or PF neurons consist of large anatomically and physiologically distinct neuronal populations that extend topographically organized projections to the striatum and provide relatively minor anatomically collaterals to and from the cerebral cortex ( Sadikot and Rymar, 2009 ; Mandelbaum et al, 2019 ; Stayte et al, 2021 ). The PF is well-positioned to reciprocally modulate information flow between the cerebral cortex and the thalamus to a certain extent ( Sherman, 2017 ; Halassa and Sherman, 2019 ).…”
Section: Introductionmentioning
confidence: 99%